ETHICAL AND LEGAL DILEMMAS OF ARTIFICIAL INTELLIGENCE: FROM COPYRIGHT TO FAIR DECISION-MAKING - NEMATJONOV, Iskandar; TO‘XTAMIRZAYEV, Shoxjaxon (YURIST AXBOROTNOMASI, 2025)
This article provides a comprehensive analysis of the ethical and legal dilemmas arising from the rapid development of artificial intelligence (AI) technologies. The primary objective of the study is to examine three pressing issues – copyright, algorithmic fairness, and liability of autonomous systems – within both the international and the national legal context of Uzbekistan. The research methodology is based on normative legal analysis, comparative legal methods, as well as the examination of international legal instruments and foreign judicial practice. The findings demonstrate that, first, the issue of authorship of AI-generated works remains unresolved under Uzbekistan’s current legislation. In this regard, the experience of the United Kingdom and China may serve as a basis for effective legal mechanisms to eliminate uncertainty. Second, algorithmic fairness and the prevention of discrimination constitute a crucial prerequisite for the protection of human rights. Accordingly, the approaches established in the EU AI Act and UNESCO’s recommendations should be adapted to the national framework. Third, the examples of autonomous transport and AI-based medical diagnostics reveal that traditional civil liability doctrines are insufficient to address the challenges of the digital era, necessitating the adoption of strict and risk-based liability regimes. The scientific novelty of this article lies in its integration of international legal practice with Uzbekistan’s national “Digital Uzbekistan – 2030” strategy, offering theoretically grounded and practically oriented proposals for legislative improvement. The conclusions of this study bear significant implications for legal doctrine, state policy, and the broader process of AI governance.